Kreativitas Guru Kelas dalam Meningkatkan Minat Belajar Membaca Siswa Kelas III di Madrasah Ibtidaiyah - Gustari, Nopian; Suradi, Ahmad; Ilusti, Ilusti (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This academic paper discusses the creativity of third-grade teachers in improving students' interest in reading at MI Negeri Bengkulu Selatan, as well as identifying the supporting and inhibiting factors for teachers' creativity in enhancing students' interest in reading. The research type is field research, which is conducted directly in the field using a qualitative research approach. Data collection techniques include observation, interviews, and documentation. The creativity of third-grade teachers in enhancing students' interest in reading includes: a) Developing teaching programs to enhance students' interest in reading, such as syllabi and lesson plans; b) Providing interesting books; c) Giving motivation, encouragement, and guidance for reading; d) Visiting the library; e) Developing learning strategies, such as introducing various books to students, including workbooks, textbook packages, comic books, storybooks, and others; f) Creating enjoyable and meaningful learning experiences, such as greeting students warmly and enthusiastically, showing appreciation, and singing together to create a joyful classroom atmosphere; g) Utilizing learning media effectively, such as visual and audio-visual media, images, and videos, and developing diverse teaching materials with attractive visuals and engaging content; g) Generating new innovations through guidance and counseling sessions. Otherwise, inhibiting factors for teachers' creativity in enhancing students' interest in reading include the lack of learning resources and available teaching media, as well as students' lack of awareness regarding the importance of reading books. Supporting factors, on the other hand, include teachers' interest in reading method books and learning strategies, as well as their active participation in KKG forums to attend training on teacher creativity.